O GERENCIAMENTO DE RESÍDUOS DE NAVIOS DE APOIO À EMPRESAS PETROLÍFERAS COM BASE NA NT 08/08: ATENDIMENTO ÀS EXIGÊNCIAS DO PROJETO DE CONTROLE DA POLUIÇÃO (PCP) / IBAMA - Ferraro, Aulus Giovani Mouzinho (2010)
It is not easy to manage a vessel in the oil business working in Brazilian waters for Petroleum Companies manly if it is a foreign vessel. One of the reasons are the several demands from IBAMA (Brazilian environmental agency) in contrast with the environmental requirements from many first world countries. This affirmative is based on foreign vessels that must obey those demands, enhance sewage treatment plants, adapt oily water separators as too the hard waste management with all reasonable evidences like photos, certificates, documents, reports etc. Particularly about the solid and liquid wastes generated offshore, IBAMA lauched NT 08/08 (Technical Note CGPEG/DILIC/IBAMA Nº 08/08) at the end of 2008 that establishes the guidelines of CGPEG Oil & Gas General Coordination to implement the Pollution Control Project (PCP) required in the process of environmental licensing for exploration and production maritime companies of oil and gas, bringing new demands to waste management issue. The Pipe Laying Support Vessels (PLSV) that work for petroleum companies in Brazil must to comply with it according the environmental contractual guidlines of your client. This work shows the challenges of the requirements attendance of IBAMA by reviewing the literature and by the presentation of cases linked to waste management and environmental management more broadly. The previous audit in the vessel out of Brazil, the noble destiny to be given to the waste and the the restriction of on board incineration in Brazil were the topics discussed in this research. The study was conducted through document review, interviews with professionals from various areas and spot checks (technical visits) consolidated on the previous experience of the author. Examples of practical application of the NT 08/08 requirements and solutions for difficulties have resulted in the work that may be useful to the environment professional and other stakeholders involved in this area.